Personalization at work : how HR can use job crafting to drive performance, engagement and wellbeing - Baker, Rob (New Delhi Kogan Page Limited, 2020)
"The potential benefits of personalization on a workforce are huge. We curate music and online streaming content to suit our own tastes and we place more value on lottery numbers we have chosen ourselves, rather than a random selection from a lucky dip. When job roles are also personalized, employees are more interested, engaged and motivated at work. The responsibility for enabling this personalization lies with HR and people professionals and a key approach to doing this is via job crafting. Personalization at Work is a practical guide explaining what job crafting is, why it's important, what the benefits are and more broadly how a personalized approach can be brought to all aspects of HR including recruitment, learning and development, performance management, diversity and inclusion and reward. Full of practical advice and case studies from companies who have already seen the benefits of a personalized approach including Virgin Money, Widerøe airlines, Logitech, Google and Connect Health, Personalization at Work is essential reading for all HR professionals wanting to improve staff engagement, retention, productivity and the overall people experience. With expert guidance on how to encourage job crafting and a personalized approach to work for employees through everything from job titles, role descriptions and benefits packages through to working patterns, flexibility and work environment, this is a book that HR and people professionals can't afford to be without"--
Includes bibliographical references and index.
Keywords: Personnel management; Quality of work life; Employee motivation; Well-being.